Metal–organic framework with optimally selective xenon adsorption and separation - Debasis Banerjee (Nature Portfolio, 2016)
Increased nuclear energy usage requires the reprocessing of used nuclear fuel to recover radioactive waste, including xenon. Here, the authors perform high-throughput computational screening to identify a metal-organic framework with high xenon selectivity, and demonstrate this with performance analysis.